Robot Beroda Perambat Dinding Berbasis Mikrokontroler ATmega 2560 Dilengkapi Kendali Nirkabel dan Penghindar Rintangan - Eko Didik Widianto; Ufan Alfianto; R. Rizal Isnanto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
This research developed a mobile wall climbing robot prototype using 4 DC motors as its driver and a suction tube. It can avoid obstacles. This robot uses Arduino Mega 2560 as its controller board. The robot's weight is 747 grams. The suction tube produces a suction force of 7.815N capable of holding the robot load in a stall vertical position using 12V of voltage. The robot able to crawl down and horizontal, but still can not climb vertically. The robot is able to receive a command of motion manually from a 2.4GHz wireless joystick. In automatic mode, the robot can avoid obstacles using the HC-SR04 proximity sensor. This research also shows the relationship between suction force and the given voltage of DC brushless motor and its throttle value.